Efeito, no coeficiente de escoamento e na vazão máxima, de medidas simplificadas de controle da geração do escoamento superficial em lote urbano - Almeida Junior, Helaelson de (2018)
As the number of impermeable surfaces in urban watersheds increases, storm drainage systems become overloaded, increasing the number of flooding events. Intending to solve, or at least mitigate such problem, studies regarding the delay of the flow through control measures in its origin have been carried out. Accordingly, the use of control measures started to be concretely considered in Brazil. Several cities have established laws and acts concerning the issues of this subject. Therefore, this paper aims to evaluate the effects of control measures at the source in a real lot, fo- cusing on simplified measures control and implantation. The chosen lot is part of a small residential complex located in the city of Maceió, state of Alagoas. It belongs to Reginaldo’s river basin, the main basin of the city. In the lot, precipitation and flow were monitored. The analysis was divided into three stages: the first, without the use of control measures and gutters on the roof of the residence; the second, with the redirection of the water through the use of gutters. It makes the water flows quickly to the street or drainage system, simulating the normal phenomenon in residences; the third, also considers the use of gutters, however, it redirects the water to permeable areas in the lot. An automatic rain gauge was installed in front of the lot to monitor the precipitation. To monitor the flow, a load sensing hydraulic pump was built, calibrated and installed. In order to evaluate the effects of the measures, a comparative analysis was made between flow coefficients considering each stage of the project. This was made using some methods to calculate the propagation of uncertainties and test the hypothesis. In addition, in order to understand the most critical events behavior, the comparative procedure was remade for the highest peak flows. The results showed that the measures implemented were ineffective for reducing the flow coefficient, showing a significant decrease (21.26%) only when the largest coefficients between stages 1 and 2 were analyzed. On the other hand, the results related with the peak flow rates were more satisfactory, reaching up to 70.71% and 50.99% of reduction between steps 1 and 3 and steps 2 and 3, respectively.